A comparison of TiF3 and NbF5 catalytic effects on hydrogen absorption and desorption kinetics of a ball-milled Mg85Zn5Ni10 alloy. Issue 60 (8th October 2018) - Yin, Yi; Li, Bo; Yuan, Zeming; Qi, Yan; Zhang, Yanghuan
Abstract : TiF3 shows better catalytic influence on hydrogen storage property of Mg85 Zn5 Ni10 than NbF5 . Abstract : In this investigation, the as-milled Mg85 Zn5 Ni10 –4C (C = TiF3, NbF5 ) composites were successfully produced via ball milling. The different influences between the catalysts TiF3 and NbF5 on the hydrogen storage behavior and microstructure of the composites were investigated by XRD, SEM, TEM and hydrogen absorption/desorption tests. The as-milled Mg85 Zn5 Ni10 –4C (C = TiF3, NbF5 ) alloys contain the major phase Mg, the secondary phase Mg2 Ni, a small amount of MgZn2, TiF3 and NbF5 . After hydrogenation, MgH2 and Mg2 NiH4 are formed, which convert back into Mg and Mg2 Ni after dehydrogenation indicating that MgZn2 and the catalysts TiF3 and NbF5 do not react with hydrogen. Compared with NbF5 catalyzed alloy, the TiF3 catalyzed alloy has a faster hydrogen absorption/desorption kinetics. On the basis of Arrhenius equation, the dehydrogenation activation energy values of the as-milled Mg85 Zn5 Ni10 –4C (C = TiF3, NbF5 ) alloys are 75.514 and 82.367 kJ mol −1 H2, respectively, while the value of ball-milled Mg85 Zn5 Ni10 alloy is 109.830 kJ mol −1 H2 . As a result, both TiF3 and NbF5 can significantly ameliorate the hydrogen storage thermodynamics. TiF3 shows better catalytic influence on hydrogen storage property of Mg85 Zn5 Ni10 than NbF5 .